Manifesto - National Alliance of Democratic Forces
001-0074-003 NATIONAL ALLIANCE OF DEMOCRATIC FORCES TO THE COUNTRY. SPANIARDS: When the Republic was attacked in July, 1936, by the old gangs which were never ready to relinquish their privileges of caste, the Spanish Democracy fought with courage and determination against the armed reaction united on the pattern of fascist principles and tactics imported from Italy and Germany. But, abandoned to struggle with her own resources while her enemies enjoyed the most generous and practical help from the totalitarian countries, the Spanish Republic was defeated in March 1939. Defeated but not vanquished because though it is true that the war had ended it does not follow that the struggle of the Spanish people against those who had snatched power by violence and treachery was at an end. The fight has never ceased, it continues with new determination with renewed faith every hour and with complete confidence in victory over the tyrants. In the penitentiaries, still overflowing with friends of freedom, in the concentration camps along all the Spanish highways, amongst the bloodiest reprisal known to all ages, amongst the most fearful and terrifying cruelties and before the indifference of the peoples of the world, continues the fight of the people. The Spaniards, alive with hope, burning with enthusiasm, the will to win deep in their hearts, have never renounced their freedom. The present stage of their long fight proceeds on the historic lines that gave it birth; opposition to fascist tyranny is only the latest form of the one that Spain has been enduring for centuries. To us, the imposition in our country of the totalitarian-national-syndicalist regime is only an accident, something temporary, that it is our right and duty to destroy. Resistance to National Fascism carefully organised inside the country has reached such a point of maturity and cuts so deep that it knows it may realise in the near future the highest of hopes. Our movement of liberation Democratic and Spanish, Spanish and Republican has all the width and complexity called for at the present time. It penetrates all the social strata and it embraces enormous proletarian masses; in its palette shine all the shades of republicanism united in a solid block, it reaches the remotest spheres of national life, and convinces those who although not belonging to a political party or sporting ideological labels, have a love for freedom, goodness and justice. Opposition is everywhere, even in the inner circle of the ruling fascist citadel. THE WHOLE OF SPAIN IS AGAINST THE FALLANGE AND ITS CRIMES. Against the torturers of Spain are all the intellectuaIs and the workers of Spain. And at the vanguard of this Spain hungry for freedom and juctice, are the directing vital organs of opinion, the republicans, the Socialists, the U.G.T. (General Workers' Union) and the C.N.T. (National Workers' Confederation). The men of the C.N.T. who, conscious of the national and world conditions, have the same outlook, the same collaborating spirit adopted during the war, will forego all but victory. They consider it their duty to pool their efforts with those of all defenders of Right and Democracy. No one will attempt to minimise the importance of the incorporation of the C.N.T. to the political movement of the organised proletariat. But next to this satisfaction, we must express our sorrow at the false position of a part of the political communist sector, stubbornly upholding a so-called Supreme Junta of National Union and taking liberties (to put it mildly) with the names of political parties and trade union organisations. We deplore such obstinacy and definitely and explicitly declare that the various forces subscribing to the present manifesto are in no way connected to the aforesaid Junta, neither do they acknowledge it. The National Alliance of Democratic Forces repudiates both the base relations with the enemy and the dangerous irresponsibility of the friend. Though it states at the same time that in this Alliance there is room, by natural right, for all those that loyally accept a National-Democratic-Republican outlook for the resolution of political and social problems. 292/946/1/75(i)